PENGARUH PEMILIHAN TEMPAT BERSALIN DI DESA MANGGIS KECAMATAN SIRAMPOG TAHUN 2008 - Malihatun Malihatun; Heni Soetikno (Universitas Harapan Bangsa Purwokerto, 2008)
Parturition safe ascertains that any rescue parturition has erudition, craft,and tool to give accomodation safe and clean, with give childbed service tomother and baby. Place parturition distinguishable be 2, namely Hospital withhelped professional energy, subsidized with complete device and at home ormother residence that will give with device does existence. Based on data that gotfrom midwife at Manggis Village Sirampog District that program executionparturition that helped by public health service has achieved 100 percents. Butthe execution around 68 percents chooses to give birth to at home, 32 percentsbirth at Hospital or in Midwife place. To detect factors backgrounding mother inplace election give birth at Mangosteen District Sirampog Village BrebesRegency Method: This watchfulness method descriptive study with approaches crossesectional. Population total that is as much as 77 person. Sample taking techniquethat is total sampling. A large part respondent chooses house as place give birth that is as much as65 respondents (84,4%). a large part respondent that choose house as place givebirth that is has education base (83,3%), correlating status doesn’t work (95,8%),low family income (93,2%), has erudition level less (95,5%) and has attitudeunfavourable (92,9%). The factors behind surface mother chooses house as place of birth that islow education factor, status doesn’t work, erudition less, and attitudeunfavourable. Keyword : Mother background, Place Selection to Birth.